Screening, Treatment, and Monitoring of Iron Deficiency Anemia in Pregnancy and Postpartum. (1st June 2022) - Elmore, Christina; Ellis, Jessica
Abstract: Iron deficiency anemia is the most prevalent form of anemia worldwide. In the United States, clinicians routinely screen for iron deficiency anemia upon initiation of prenatal care, at the start of the third trimester, and prior to birth. Treatment of iron deficiency anemia generally begins with oral supplementation of elemental iron, which is associated with adverse gastrointestinal effects. These adverse effects can decrease adherence, leading to subtherapeutic treatment. Newer evidence highlights the benefits of early screening for iron deficiency before the onset of anemia, as well as the use of intravenous iron to expedite the treatment of iron deficiency anemia. More research is needed on the potential consequences of over‐supplementation and iron deficiency without anemia to guide treatment. This article reviews the evidence for best practices for screening, treatment, and continued monitoring of iron deficiency anemia during pregnancy and postpartum. Maternal, fetal, and neonatal implications are reviewed, as well as the risks and benefits of treatment options. Finally, an evidence‐based algorithm is proposed to guide clinicians on continued monitoring after treatment.